PERLINDUNGAN HUKUM TERHADAP KORBAN DARI KEKERASAN DALAM RUMAH TANGGA AKIBAT PERKAWINAN DI BAWAH UMUR - Laurentius Albert; Mety Rahmawati (Jurnal Hukum Adigama, 2018)
Nowadays, child marriage has risen sharply, although there had been an age limit to marry in the law number 1 of 1974 about marriage in article 7 paragraoh (1). Child marriage happened because of some factors which is Internal factors and external factors. These days there are many parties have been marriage under the age limit and it caused by the lack of knowledge and readiness physical or mental in overcoming households problem which then lead to violence or that which disbeut domestic violence. Some particular case verdict number 260/Pid.Sus/2017/PN Jpa, verdict 94 / Pid. Sus / 2015 / PN. Srg, and medical report number R/07/I/2016/SPK/RestaBalam. Those three cases is the under age married couple that eventually use verbal abuse or diss that lead to violence and even death. To overcome the domestic violence, government had form the law number 23 of 2004 concerning the elimination of domestic violence, he act of number 31 of year 2004 on witness protection and the, the law number 39 of 1999 concerning human rights and also institution of witness protection and the to protect the victims of domestic violence especially for women and kids for marriage under age. Even though there are laws that regulate about the protection of victims, however In fact still many of the victims were not figure out how to the protection law , this gave rise to intention for writer to assess deeper on protection laws against the victims of domestic violence especially occurring in marriage under age.